Konsep Kurikulum Madrasah, Sekolah, dan Pesantren di Indonesia - Kusuma, Muhammad Galih; Musthofa, Fu’ad Zaky; Khuriyah, Khuriyah (Lembaga Yasin AlSys, 2025)
The madrasah, pesantren, and public school curricula have their own characteristics that reflect the goals that the three educational institutions want to achieve. The research method used in this research is a literature study where this approach aims to examine and review various relevant literature sources related to the concept of the Pesantren, Madrasah, and School curriculum. these three curricula complement each other in creating a holistic learning environment. Although they have different focuses and approaches, their ultimate goal remains the same: forming individuals who are not only academically intelligent, but also have integrity and a strong personality. This reflects the importance of a balanced education between knowledge, skills and moral values as a provision to face challenges in an ever-changing world.